The Association between Serum Lipid Profile and Retinopathy in Type 2 Diabetes Mellitus Patients (Academia Journal of Medicine, 2019)
Background: Blood such as VLDL, intermediate density lipoprotein (IDL), chylomicrons, chylomicron remnants and lipoprotein and  therefore provides a more accurate estimate of CV risk than LDL-C alone, as shown in numerous epidemiological and clinical studies. This is  particularly true for patients who are already on statin therapy or those with elevated levels of VLDL-C such a patients with obesity, metabolic  syndrome and diabetes. Subjects and Methods: A pre-structural proforma was used to collect baseline date detailed clinical history with  clinical examination and relevant investigation was done on participating individuals. Results: Significant correlation between HbA1c and  various circulating lipid parameters and significant difference of lipid parameters in two groups (7.0%) of glycated haemoglobin  indicates that HbA1c can be used as a potential biomarker for predicting dyslipidemia in type 2 diabetic patients. Conclusion: As good control  of diabetes is shown to keep the lipid levels in near normal range, it appears important to aim at critical control of DM to prevent or at least  postpone the onset of various complications.
Keywords: Dyslipidemia; Hba1c; Lipid Parameters